Hyperboles Used by Rin Hermana and Ge Pamungkas’s Stand Up Comedy in Kompas Tv - Rani, Sherly Nia; Refnaldi, Refnaldi (English Language and Literature, 2020)
In language study, figurative language is language that uses words or expressions with a meaning that is different from the literal interpretation. Hyperbolic expression is one kind of figures of speech that exaggerates things with overstatement. In this research focuses with hyperboles used by Rin Hermana and Ge Pamungkas’s Stand Up Comedy in KompasTV. The purpose of this research are to describe the form of hyperbole and the hyperbolic meaning used by Rin Hermana and Ge Pamungkas in the video which is downloaded from YouTube based on theory of Claridge. The types of the research in this study are qualitative and quantitative method. Qualitative research is used to analyze the data in the form text and quantitative research is used to calculate number of forms of hyperboles and types of hyperbolic meaning in Rin Hermana and Ge Pamungkas’s Stand Up Comedy video to conclude which dominantly used. To find out the data of hyperboles, the researcher used checklist method and color coding. This study found that there are 7 forms of hyperbole and also 7 types of hyperbolic meaning. This study shows, the dominant forms by both Stand Up Comedian is repetition and the dominant types of hyperbolic meaning is connotative meaning. Keywords: Figurative Language, Hyperbole, Stand-Up Comedy.